Inequitable use of health services for Indigenous mothers who experience stillbirth in Australia. Issue 2 (7th October 2021) - Callander, Emily; Fox, Haylee; Mills, Kyly; Stuart‐Butler, Deanna; Middleton, Philippa; Ellwood, David; Thomas, Joseph; Flenady, Vicki
Abstract: Objectives: The purpose of this study was to identify differences in health service expenditure on Indigenous and non‐Indigenous women who experience a stillbirth, women's out‐of‐pocket costs, and health service use. Methods: The project used a whole‐of‐population linked data set called "Maternity1000, " which includes all women who gave birth in Queensland, Australia, between July 1, 2012, and June 30, 2018 (n = 396 158). Multivariable analysis was undertaken to assess differences in mean health service expenditure; and number of health care services accessed between Indigenous and non‐Indigenous women who had a stillbirth from birth to twelve months postpartum. Costs are presented in 2019/20 Australian dollars. Results: There was a total of 1864 babies stillborn to women in Queensland between July 1, 2012, and June 30, 2018, with 135 being born to Indigenous women and 1729 born to non‐Indigenous women. There was significantly lower total expenditure per woman for Indigenous women compared with non‐Indigenous women ($16 083 and $18 811, respectively). This was consistent across public hospital inpatient ($12 564 compared with $14 075), outpatient ($1127 compared with $1470), community‐based services ($198 compared with $313), pharmaceuticals ($8 compared with $22), private hospital ($434 compared with $1265), and for individual out‐of‐pocket fees ($21 compared with $86). Mean expenditure on emergency department services per woman was higher for Indigenous women compared with non‐Indigenous women ($947 compared with $643). Indigenous women who experienced a stillbirth accessed fewer general practitioners, allied health, specialist, obstetrics, and outpatient services, and fewer pathology and diagnostic test than their non‐Indigenous counterparts. Conclusions: Inequities in access to health services exist between Indigenous and non‐Indigenous women who experience a stillbirth.